Usaha Mikro Kecil dan Menengah (UMKM) Dalam Peranan Digital Marketing - wafa, Azimul; Sultan Mubarok, Muhammad; Effendi, Bahtiar (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The development and advancement of the current era are inseparable from the digital world where the digital world has also changed the view of the world of marketing, the flow of marketing has moved from conventional to digital, and the impact is very pronounced where the current era of more effective marketing makes it possible for buyers to have and see information about products easily and quickly and can be done anywhere and anytime, customer searches with this online media are called digital marketing, even this development has made changes where small UMKM can be left behind and lost due to lack of knowledge of the internet in the era of rampant online shops such as TikTok stores, Shopee, Lazada and so on. This writing is taken on a qualitative approach where it provides an explanation of the object of research and makes observations at the level of UMKM in the area from a small scale, satisfaction is one of the successes in this digital era in developing UMKM actors in build and provide progress in their products and the existence of the digital era is one of the challenges for UMKM actors because they interact directly from various online circles, opening up opportunities for UMKM actors to get more benefits with customers from very many online users, implementing into the real world where the advancement of UMKM technology can be more advanced and not left behind in the online shop introduction to UMKM about digital marketing has a significant impact.